Respon Penambahan Proporsi Bubur Rumput Laut Dengan Tepung Tapioka dan Konsentrasi Ekstrak Sawi Terhadap Mutu Bakso Ayam - Tri Mahdiyahtul Faricha; Sri Winarsih; Elfi Anis Saati (Universitas Muhammadiyah Malang, 2019)
Meatballs are round or other food products derived from cattle meat mix (not less than 50% meat content) and starch or cereals with or without the addition of other food ingredients and permissible dietary ingredients. Meatballs in general have a rubbery texture approaching hard and have a less attractive color that needs to be done production innovation, one of them is by addition of green mustard extract with the composition of seaweed porridge and tapioca flour. This study aims to determine the effect of interaction between the proportion of seaweed porridge with tapioca starch and extract concentration, and each of these factors. The research was conducted by using Group Random Design (RAK) two factors. The factor I with 4 levels is the composition of seaweed porridge with tapioca flour, among others: 5%: 25%, 10%: 20%, 15%: 15%, 20%: 10%. Factor II with 3 levels is the addition of green mustard extract concentration (1: 1, 2: 1, 3: 1). Meatball testing is done on physicochemical properties (moisture content, ash, protein, fat, carbohydrate, antioxidant, total chlorophyll, texture, and color) and organoleptic (taste, aroma, joy, suppleness, and appearance. The results showed that interaction between substitution of seaweed with green bean extracts dye to moisture content, ash content, yellowishness (b+), total chlorophyll, antioxidant, taste score, elasticity score, appearance score, and no effect on protein content, brightness (L), yellowishness (a-), aroma score, favorite score. The best treatment of chicken meatball was obtained from R4S3 treatment with the addition of 20% seaweed porridge with 10% tapioca starch and 3: 1 green mustard concentration with 74.20% moisture content, 2.62% ash content, 2.53 fat content %, protein content 17.45%, carbohydrate 20.32%, chlorophyll 0.47 mg / L, and antioxidant 75.73%, texture of 4.96, brightness level (L) 62.47, yellowishness -) 7.07, greenishness (b +) 12.83. Furthermore, organoleptic test with organoleptic score 2.60 (enough), taste score 2.67 (good enough), aroma score 2.70 (quite like), the score of 2.90 (quite interesting), and score suppleness 2.83 (quite chewy). All of the parameters tested such as moisture content, ash content, protein content, and fat content have fulfilled SNI 01-3818 of 1995 chicken meatball.